Development Of E-LKPD Based On Vee Diagram To Facilitate Student Metacognitive - Ridwanty, Andini Silvia (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2025)
Conscious management of thought processes is still a major challenge for many students, especially in biology learning. Based on the analysis, there is no E-LKPD available in schools that facilitates students' metacognitive abilities optimally, especially in class XI high school human reproductive system material. Therefore, this research aims to develop a Vee Diagram-based E-LKPD that integrates Problem Based Learning (PBL) syntax so that students can manage their thinking processes independently. This research is Research and Development (R&D) research with the ADDIE model. The instruments used were material, education and media expert validation, student response questionnaires, learning observation sheets, and the Metacognitive Awareness Inventory (MAI) questionnaire. The validation results show that the E-LKPD is very feasible in terms of content, presentation and media appearance. Trials on class XI students resulted in an effective response of 75.72%, with learning syntax implementation reaching 97%. The results of the Metacognitive Awareness Inventory (MAI) questionnaire showed an increase in the planning, monitoring and self-evaluation aspects, with the highest gain in the planning aspect (0.90). Thus, E-LKPD is feasible and effective for improving students' metacognitive abilities